Effect of trimetaphosphate and fluoride association on hydroxyapatite dissolution and precipitation in vitro - Delbem, Alberto Carlos Botazzo [UNESP]; Souza, José Antonio Santos [UNESP]; Zaze, Ana Carolina Soares Fraga; Takeshita, Eliana Mitsue; Sassaki, Kikue Takebayashi [UNESP]; Moraes, João Carlos Silos [UNESP] (FapUNIFESP (SciELO), 2014)
The present study analyzed the action of sodium trimetaphosphate (TMP) and/or fluoride on hydroxyapatite. Hydroxyapatite powder was suspended in different solutions: deionized water, 500 µg F/mL, 1,100 µg F/mL, 1%TMP, 3%TMP, 500 µg F/mL plus 1%TMP and 500 µg F/mL plus 3%TMP. The pH value of the solutions was reduced to 4.0 and after 30 min, raised to 7.0 (three times). After pH-cycling, the samples were analyzed by X-ray diffraction and infrared spectroscopy. The concentrations of calcium fluoride, fluoride, calcium and phosphorus were also determined. Adding 1% or 3% TMP to the solution containing 500 µg F/mL produced a higher quantity of calcium fluoride compared to samples prepared in a 1,100 µg F/mL solution. Regarding the calcium concentration, samples prepared in solutions of 1,100 µg F/mL and 500 µg F/mL plus TMP were statistically similar and showed higher values. Using solutions of 1,100 µg F/mL and 500 µg F/mL plus TMP resulted in a calcium/phosphorus ratio close to that of hydroxyapatite. It is concluded that the association of TMP and fluoride favored the precipitation of a more stable hydroxyapatite.

O presente estudo avaliou a ação do trimetafosfato de sódio (TMP) e/ ou fluoreto sobre a hidroxiapatita. Pó de hidroxiapatita foi suspenso em diferentes soluções: água deionizada, 500 µg F/mL, 1100 µg F/mL, 1%TMP, 3%TMP, 500 µg F/mL adicionado a 1%TMP e 500 µg F/mL associado a 3%TMP. O pH das soluções foi reduzido para 4,0 e depois de 30 min, elevado para 7,0 (três vezes). Depois do processo de ciclagem de pH, as amostras foram analisadas por difração de raios-X e espectroscopia por infravermelho. As concentrações de fluoreto de cálcio, fluoreto, cálcio e fósforo também foram determinadas. A adição de 1% ou 3% TMP na solução contendo 500 µg F/mL produziu uma maior quantidade de fluoreto de cálcio comparado às amostras tratadas com uma solução de 1100 µg F/mL. A respeito da concentração de cálcio, amostras tratadas com soluções de 1100 µg F/mL e 500 µg F/mL adicionado ao TMP foram estatisticamente similares e mostraram maiores valores. Soluções de 1100 µg F/mL e 500 µg F/mL adicionado ao TMP resultaram em uma proporção molar Ca/P mais próxima à da hidroxiapatita. Conclui-se que a associação de TMP e F favoreceu a precipitação de uma hidroxiapatita mais estável.
Keywords: Hydroxyapatite; Polyphosphates; Demineralization; Solubility; Fluoride